Moderasi Beragama dalam Perbedaan Idulfitri Komunitas Muslim Buano Utara: Studi Netnografi - Shafiya Nabila; Zaskia Icha Ramadhani; Neila Febriyanti Putri Zakis; Reggina Jesy Prabawan; Aulia Rizqi Arinda; Fadhilatul Akmalia; Arini Rahma Maftukha; Fikroh Zanani; Davina Wirda; Arditya Prayogi (Islamuna: Jurnal Studi Keislaman, 2026)
This article examines religious moderation in the different determination of Eid al-Fitr 1447 H in Buano Utara Village, West Seram Regency, Maluku, with attention to the tension between local religious authority and digital public judgment. The study uses a qualitative netnographic method because the available data are centered on social media reports, video fragments, public comments, and supporting literature on local Islamic traditions and religious moderation. Data were interpreted through the indicators of religious moderation, digital religion studies, iceberg analysis, and Theory U. The findings show that the local Muslim community practiced Eid earlier through rukyat bil fi'li rooted in inherited knowledge and recognized by local religious-adat authorities. At the village level, the difference did not trigger social boycott or physical conflict; instead, it displayed tolerance, non-violence, respect for local wisdom, and communal maturity. The digital sphere presented a different pattern: several comments framed the practice as invalid, strange, or deviant. This contrast reveals an asymmetry between lived moderation in local society and weak digital religious literacy. The article argues that Islamic education should treat this case as a learning resource for adab al-ikhtilaf, tabayyun, and digital ethics, so that methodological differences in worship are not converted into stigma or symbolic violence.